2017
DOI: 10.1097/qad.0000000000001307
|View full text |Cite
|
Sign up to set email alerts
|

Has the phasing out of stavudine in accordance with changes in WHO guidelines led to a decrease in single-drug substitutions in first-line antiretroviral therapy for HIV in sub-Saharan Africa?

Abstract: OBJECTIVE We assessed the relationship between phasing out stavudine in first-line antiretroviral therapy(ART) in accordance with World Health Organization 2010 policy and single-drug substitutions (SDS)(substituting the nucleoside reverse transcriptase inhibitor(NRTI) in first-line ART) in sub-Saharan Africa. DESIGN Prospective cohort analysis (IeDEA-Multiregional) including ART-naïve, HIV-infected patients ≥16 years initiating ART between January 2005-December 2012. Before April 2010 (July 2007 in Zambia) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…As changes in the trends of substitutions, treatment interruptions and second‐line switches for sex and age (<10 vs. >10 years) could vary by NRTI used in first‐line ART, we calculated the risk due to interdependence (R(I)). Similar to prior adult work , we here show a positive interdependence for female gender and stavudine use in first‐line ART for two of the three primary outcomes (single‐drug substitution: 6.4% [difference in RD: 0.132–0.067] and second‐line switches: 5.6% [difference in RD: 0.003 to −0.053]). Therefore, 6.4% of single‐drug substitutions in female patients on stavudine is related to the dual action of female gender and stavudine.…”
Section: Resultssupporting
confidence: 84%
“…As changes in the trends of substitutions, treatment interruptions and second‐line switches for sex and age (<10 vs. >10 years) could vary by NRTI used in first‐line ART, we calculated the risk due to interdependence (R(I)). Similar to prior adult work , we here show a positive interdependence for female gender and stavudine use in first‐line ART for two of the three primary outcomes (single‐drug substitution: 6.4% [difference in RD: 0.132–0.067] and second‐line switches: 5.6% [difference in RD: 0.003 to −0.053]). Therefore, 6.4% of single‐drug substitutions in female patients on stavudine is related to the dual action of female gender and stavudine.…”
Section: Resultssupporting
confidence: 84%
“…In Uganda from 2003 to 2008 the typical ART regimens included stavudine or less frequently zidovudine, plus lamivudine plus nevirapine or efavirenz [6]. In 2008 the Uganda Ministry of Health (MoH) recommended a systematic national drug substitution from stavudine to other nucleoside/nucleotide reverse transcriptase (NRTI) regardless of the presence of toxicities [7, 8], preceding the 2010 WHO recommendation of replacing stavudine with zidovudine or tenofovir [9]. Tenofovir is an nucleotide reverse transcriptase inhibitor which has shown a better safety profile than stavudine and zidovudine [2], and several observational studies demonstrated that modifications in the first 2–3 years on ART due to toxicities are less frequent in patients started on tenofovir [5, 8, 1013].…”
Section: Introductionmentioning
confidence: 99%
“…As seen in previous South African studies we found a much lower rate of treatment discontinuations with tenofovir than with stavudine. [ 9 , 19 ]…”
Section: Discussionmentioning
confidence: 99%